Encapsulated fronds technology modified for long-term preservation of Lemna aequinoctialis - Hoàng, Thị Như Phương (Springer Netherlands, 2025)
Duckweeds, the Lemnaceae family, are employed in a wide range of industries, including agriculture, animal feed, wastewater treatment, biofuel production, and human food. Duckweeds are also of interest for researchers. However, due to their rapid growth, development, and susceptibility to contamination by bacteria and algae during the storage process, duckweed samples require a great deal of time and effort to be maintained. In order to overcome the difficulties in preserving duckweed samples for scientific research, we developed an approach for duckweed storage by modification of the ‘artificial seed’ procedure. We found that encapsulation of entire fronds of Lemna aequinoctialis in Na-Alginate (3, 4, and 5%) and calcium chloride (150, 200, and 250 mM) were appropriate for maintaining them in a metabolically reduced state. After being stored for two months, there were no obvious variations between artificial seeds having an endosperm composition of ½ “N” medium, “N”, and water. After two months, duckweed samples kept in seeds with “N” endosperm medium containing 150 mM CaCl2 and 3% sodium alginate recovered the best. Following a year of storage, a noticeable difference could be seen between the treatments with various endosperm medium compositions. The optimal conditions were encapsulation in an aqueous medium containing 200 mM CaCl2 and 3% sodium alginate. This procedure offers an effective, cost-saving long-term preservation strategy that may be adapted in future for further duckweed species.